The main features of socio-cultural relationships in Swedish and Russian communicative behavior - A Y Arkhipenkova (Russian journal of linguistics: Vestnik RUDN, 2011)
The article examines differences in socio-cultural relationships in Russian and Swedish communicative behaviour. The author identifies the main national and cultural values in these cultures.